Pengenalan Bunga Telang (Clitoria ternatea L.) di Desa Wisata Alam Sungai Masjid Kabupaten Dumai sebagai upaya membantu peningkatan Hospitality - Ninik Nihayatul Wahibah; Delita Zul; Atria Martina; Yulminarti Yulminarti; Ennie Chahyadi; Yuana Nurulita (Unri Conference Series: Community Engagement, 2021)
Kelompok Sadar Wisata or Tourism Awareness Group (POKDARWIS) Desa Wisata Sungai Masjid Kabupaten Dumai have been improving their rural tourism. One of their services for tourists or guests is providing welcome drinks. Therefore, the objective of our program was to introduce butterfly pea, how to plant and how to utilize the flowers particularly for improving hospitality such as welcome drink and welcome kit. Butterfly pea (Clitoria ternatea L.) plants are known relatively easy to grow and possess chemical properties good for human health. We delivered our program to POKDARWIS Desa Wisata Sungai Masjid ss our partner through the oral presentation and demonstrated video. We also gave seeds and seedlings of butterfly pea to the participants. Our partners did not know about butterfly pea flower before participating in our program. They showed their enthusiasm and curiosity, particularly during the discussion session. Results of the questionnaire indicated that our program was useful to enhance their knowledge and provide inspiration to improve their life. One week later, after the training, the POKDARWIS had their program which adopted our program such as sowing and planting butterfly pea seeds and seedlings. Based on the results, we conclude that we have conveyed our program successfully and inspired our partners to produce butterfly pea-based food and beverages.